2020
DOI: 10.17263/jlls.803748
|View full text |Cite
|
Sign up to set email alerts
|

The role of literature and literary texts in an EFL context: Cultural awareness and language skills

Abstract: This research was aimed to 1) investigate the attitudes of learners towards literature, and 2) discover the impact of literature and literary texts on cultural awareness and language skills in Thai EFL undergraduate students. A blend of qualitative and quantitative research configuration was embraced. An abstract content was coordinated into an EFL class with 100 English major students at Buriram Rajabhat University. It is one of universities in the Northeast of Thailand. The samples were chosen by a simple ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Based on the research findings, it can be understood that the usage of literature has a great effect on culture as it reflects a lot of traces related to people, traditions and differences. The integrated use of literature and literary texts in an EFL classroom allows learners to improve their linguistic abilities while also increasing their knowledge of culture (Isariyawat, C. Yenpheech, C. & Intanoo, K., 2020). The findings indicate that the students think the usage of literary texts develop their language skills, personal involvement and cultural awareness, so literary texts are useful in terms of second language acquisition.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Based on the research findings, it can be understood that the usage of literature has a great effect on culture as it reflects a lot of traces related to people, traditions and differences. The integrated use of literature and literary texts in an EFL classroom allows learners to improve their linguistic abilities while also increasing their knowledge of culture (Isariyawat, C. Yenpheech, C. & Intanoo, K., 2020). The findings indicate that the students think the usage of literary texts develop their language skills, personal involvement and cultural awareness, so literary texts are useful in terms of second language acquisition.…”
Section: Discussionmentioning
confidence: 89%
“…The results suggest that the research was precious and useful, and thus, literary texts should be included in the second language teaching curriculum. When the results are compared to the findings taken from Isariyawat, C. et. al.…”
Section: Discussionmentioning
confidence: 95%
“…The Cultural Model, or language as content (Lazar, 1993), is a traditional approach to teaching literature (Hadjoui & Kheladi, 2014) where learners are supposed to find out about the text's context from different perspectives: social, political, literary and historical (Rahimipour, 2019). In the words of Isariyawat et al (2020), "it [the cultural model] urges understudies to find and investigate social, literary and recorded components of the content" (p. 1323). Not only does the cultural model show the universality of thoughts and ideas, but it also promotes learners' awareness of those cultures and ideologies that are different from theirs (Yimwilai, 2015).…”
Section: Literature Review the Cultural Approachmentioning
confidence: 99%
“…For Fehaima (2018), the language-based model paves the way for learners to increase their understanding of language by confronting them with various themes and topics. Though there are a few literary goals that are expected to be achieved in this model, overall, the study of language overrides that of literature (Isariyawat et al, 2020;Rahimipour, 2019). This means that, insofar as language is concerned, opting for the language-based approach to teaching literature would be the right choice (Rahimipour, 2019).…”
Section: The Language-based Modelmentioning
confidence: 99%
“…She further concluded that unknown and new cultural concepts could promote students' interest, interpretive stance and cultural awareness provided the background information related to the texts were pre-taught and explained to the students. Isariyawat et al (2020) also examined the students' attitudes towards literature, however, they added the elements of language skills in this study which was carried out among undergraduate students in Thailand. They discovered that the respondents felt that literary texts could help them develop the language skills; especially speaking, listening and reading skills, in which the students could sustain their discussions over a longer period and their perusing capacity had greatly improved when they read short stories or novels.…”
Section: Literature Reviewmentioning
confidence: 99%